Analisis Yuridis Terhadap Penetapan Batas Waktu Surat Kuasa Membebankan Hak Tanggungan (SKMHT) Untuk Menjamin Pelunasan Kredit Tertentu Studi Putusan ”21/Pdt.G/2019/PN.Tka” - Habiba; Abdul Kadir; Karmila (Pledoi Law Jurnal, 2023)
ABSTRACT: Credit is a financial facility in which a person or business entity borrows money and repays it within a specified period of time and bears interest. This study aims to find out the basis for the judge's considerations in case number